First report of a histozoic Henneguya (Cnidaria, Endocnidozoa) infecting a synbranchid potamodromous fish from South America: Morphostructural and biological data - Mathews, Patrick D. [UNESP]; Mertins, Omar; Espinoza, Luis L.; Aguiar, Julio C. [UNESP]; Milanin, Tiago (Pensoft Publishers, 2023)
In this study, a Henneguya myxosporean species is described to infect an ecological, biological, and evolutionary important fish from Amazon biome. The myxosporean was found in the skin of only one specimen of marbled swamp eel, Synbranchus marmoratus caught in a small stream from Peruvian Amazon floodplain. Mature myxospores have ovoid shape from the valvular view, measuring 32.2 ± 0.6 μm (31.6–32.8) in total length, 21.5 ± 0.3 μm (21.2–21.8) in spore body length, 11.7 ± 0.5 μm (11.2–12.2) in width and 10.6 ± 0.9 μm (9.7–11.5) in thickness. Non-bifurcate caudal appendage, measuring 10.7 ± 0.4 μm (10.3–11.1) in length. Two polar capsules elongated aubergine in shape, equal in size and measuring 4.9 ± 0.2 μm (4.7–5.1) in length and 3.1 ± 0.5 μm (2.6–3.6) in width. Polar tubules coiled in 7–8 turns. This is the first report of a Henneguya species parasitizing a fish of the order Synbranchiformes from Amazon basin and the first to describe this parasite infecting a potamodromous fish from South America.
Keywords: Henneguya; marbled swamp eel; myxosporean; Peru; skin